Hermano [videorecording (DVD)] - Rasquin, Marcel; Armas, Eliú; Rondon, Alí (Actor) (Music Box Films, 2012)
Raised as brothers, intense teammates and competitors on the soccer field, the gregarious, swaggering Julio and the wiry, focused Daniel have remained virtually inseparable ever since the newborn Daniel was found abandoned in a trash heap in their La Ceniza slum.